Validation of 5G Use Case Solutions – Simultaneous Assessment of Business Value and Social Acceptance in Early Stages of the Research and Innovation Projects - Nesse, Per J.; Hallingby, Hanne Stine; Briguglio, Luigi; Markopoulos, Ioannis (Nordic and Baltic Journal of Information & Communications Technologies, 2023)
This article recommends a lean approach when validating next generation mobile technology (5G) use case solutions in research and innovations projects (R&I). This validation should include a simultaneous and iterative assessment of business value and social acceptance beyond the traditional assessment of technological performance. The context studied in the article is R&I projects funded by the European Commission. Here a consortium of academic and enterprise partners jointly develops 5G product and service solutions for different industry verticals. From the literature review we learn that partnerships and ecosystems accelerate innovations as well as the significance of performing the validation already in the initial steps of the innovation projects. Based on a case study of seven completed 5G R&I projects we revealed that lean methodology for development of use case solutions were not applied. Furthermore, the assessment of potential business values from the 5G use case solutions, was postponed to the later stages of the R&I projects, and that assessing the social acceptance of these solutions were absent. After piloting the lean start-up methodology in an ongoing 5G R&I project (5G SOLUTIONS) we found that the partners advocated technological performance, business value and social acceptance to be ranked equally important to successfully validate the 5G use case solutions in the early steps in the innovation process. The two pilots we executed was performed as online workshops with partners from the 5G SOLUTIONS consortium and the media and entertainment vertical. The prototype was presented and feedback from the stakeholders were collected using surveys and interactive software tools. We recommend further studies and pilots of our lean start-up validation methodology in forthcoming 5G R&I projects funded by Horizon Europe for confirmation of our findings and further refinement.